(untitled) (The Lumbini Journal of Business and Economics, 2023)
Information is power and power is information. Without information there can be no growth. Now information is penetrating into rural India as well, because without its presence there, we cannot think about development of the entire country. India is in the midst of a knowledge revolution, complemented by the opening up of entirely new-vistas in information and communication technology. Information and Communication Technology (ICT) has emerged as an effective facilitator in the development of any society and is a prime driving force in the growth of rural economies. The Rural Market of India is showing an impressive growth largely due to changing lifestyle patterns, better communication network and rapidly changing demand structure of consumers of rural area. With the changing patterns of Rural Market, the role of ICT has increased from providing only the Networks to set-up the basis of updated technological programs in the rural area. It is widely believed that Information and Communications Technologies (ICTs) are effective tools in the development of rural India. Rural people are less knowledgeable rather than their city counterparts. Thus, technological advancement is necessary for every nook and corner of India.